HUBUNGAN GEGURITAN BRAYUT DENGAN SOSIAL BUDAYA MASYARAKAT BALI - A.A. Diah Indrayani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Literature and culture have the same object that is a human being which existed in a community as a social fact and as a cultural creature. They have a special place in a society due to their close relationship. The figure can be found on a various art creations in Bali such as painting, sculpture and traditional song. Meanwhile, the government promotes family planning as a program to the citizen. The problems discussed on this research is how the relation between geguritan Brayut and social and cultural of the Balinese. The methodology of this study is a qualitative research through non-interactive research by analyzing a textual research which is not related to the community on its organic environment. The research approach used in this study is thematic philosophy. The theory applied in this research are theory of deconstruction and semiotic. The result of this research shows that the relation between Geguritan Brayut with social and culture of Balinese community can be seen on their marriage concept according to Hindu belief, family prosperity, child nurture, the genetic system (matrilineal and patrilineal).